Measuring salsalate solubility in supercritical carbon dioxide: Experimental and thermodynamic modelling. (January 2021) - Zabihi, Samyar; Jamshidian, Sahar; Borousan, Fatemeh; Zeinolabedini Hezave, Ali; Pishnamazi, Mahboubeh; Marjani, Azam; Shirazian, Saeed
Highlights: Measuring salsalate solubility in supercritical CO2 . Mathematical modelling drug solubility using semi-empirical models. Studying the influence of pressure and temperature on salsalate solubility. Abstract: Solubility of salsalate, known as 2-carboxyphenyl salicylate and salicylsalicylic acid, in supercritical carbon dioxide was obtained. The measurements were carried out at different conditions, i.e. pressures = 12.0–40.0 MPa, and temperatures = 308–338 K. Both theoretical and experimental works were conducted to measure and understand the correlation of solubility with thermodynamic parameters, i.e. T and P . The results indicated that the measured solubility lies between (3.77 × 10 −5 to 3.88 × 10 −3 ) in mole fraction to reveal significant and direct influence of pressure on the salsalate solubility. On the other hand, the examined temperatures introduce dual effect on the solubility of this drug. Furthermore, the obtained data confirm existence of a cross-over point at around 16.0 MPa in which the effect of temperature change from the solubility retarding effect to the solubility boosting effect. To investigate theoretically the solubility, the measured results are successfully correlated by 5 semi-empirical density-based models: viz. Chrastil, Garlapati and Madras, Mendez-Santiago and Teja (MST), Bartle et al., and Kumar and Johnston (KJ) models among which the KJ model indicated the minimum average absolute relative deviation percent (AARD%) of about 8.26%. Finally, a self-consistency test was carried out based on MST correlation, and demonstrated that not only the correlation used is capable to correlate the experimental solubility, but also it is viable to extrapolate the drug solubility data which is a considerable capability for these simple correlations.